Fuzzy neighborhood structures on partially ordered groups - Kamel El-Saady; M. Y. Bakier (International Journal of Mathematics and Mathematical Sciences)
Ahsanullah (1988) showed the compatibility between group structures and I-fuzzy neighborhood systems. In this paper, we require not only that the I-fuzzy neighborhood systems be compatible with the group structures, but also compatible with the order relation, in one sense or another.